Laser guide star return-flux gain from frequency chirping. Issue 3 (9th February 2022) - Hellemeier, J; Enderlein, M; Hager, M; Bonaccini Calia, D; Johnson, R L; Lison, F; Byrd, M O; Kann, L A; Centrone, M; Hickson, P
ABSTRACT: Spectral hole burning reduces sodium laser guide star efficiency. Due to photon recoil, atoms that are initially resonant with the single-frequency laser get Doppler shifted out of resonance, which reduces the return flux. Frequency-chirped (also known as frequency-swept) continuous-wave lasers have the potential to mitigate the effect of spectral hole burning and even increase the laser guide star efficiency beyond the theoretical limit of a single-frequency laser. We investigate the return flux of frequency-chirped laser guide stars and its dependence on environmental and chirping parameters. On-sky measurements of a frequency-chirped, single-frequency laser guide star are performed at the Roque de los Muchachos Observatory on La Palma. A fast photon-counting receiver system is employed to resolve the return-flux response during laser frequency sweeps gaining insights into the population dynamics of the sodium layer. At a launched laser power of 16.5 W, we find a maximum gain in return flux of 22 per cent compared to a fixed-frequency laser at a chirping amplitude of the order of 150 MHz and a chirping rate of 0.8 MHz µs −1 . Time-resolved measurements during the chirping period confirm our understanding of the population dynamics in the sodium layer. These are the first measurements of return-flux enhancement for laser guide stars excited by a single-frequency-chirped continuous-wave laser. For higher laser powers, the effectiveness of chirping is expected to increase, which could be highly beneficial for telescopes equipped with high-power laser guide star adaptive optics systems.